Analysis of Oil Content, Plankton and Macrozoobenthos Communities Structure in Liung River Waters Bengkalis Regency - Antoni Antoni; Aras Mulyadi; Sofyan Husein Siregar (Jurnal Ilmu Lingkungan, 2017)
This research was conducted in November 2015 until February 2016 located at Liung River waters Bantan District Bengkalis Riau Province with the aim to analyze the oil content in water and aquatic sediments, the structure of the plankton community and macrozoobenthos. The survey method was applied in this research with four research stations as sampling point. Samples were analyzed in the Laboratory of Ecology and Environmental Management of Water and Food Chemistry Laboratory of the Faculty of Fisheries and Marine Sciences of the Riau University. The results showed that the oil content in water ranged from 0.225 to 0.325 ppm and in sediments ranged from 447.67 to 582.33 ppm. The high oil in the sediment is possible because the oil accumulates in the sediments that are affected by the current state. The abundance of plankton ranged from 1200 to 4266.67 cells/L and found 18 genera with index of diversity index (H') 2.5022 to 2.9477, dominance index (C) 0.1481 to 0.2524 and index of uniformity (E) 0.7533 to 0.9299. Similarly, the abundance of macrozoobenthos ranged from 55 to 82.33 Ind/m2 and found 10 genera with diversity index (H') 0.9169 to 2.2489, dominance index (C) 0.2231 to 0.5565 and index of uniformity (E) 0.9169 to 1. The regression analysis between oil content in coloum water with plankton abundance shows negative correlation (Y = 5811.383 – 10167.685X; R2 = 0.353; r = 0.594) and oil content in sediment with macrozoobenthos abundance also show negative correlation (Y = 120.923 – 932.202X; R2 = 0.511; r = 0.715).